Determination of energy use efficiency and greenhouse gas emissions in peach production - Demir, Cihan; Gökdoğan, Osman (International Journal of Agricultural and Biological Engineering, 2023)
The purpose of this study is to determine the energy use efficiency and greenhouse gas (GHG) emissions in peach production that took place in Kırklareli province of Turkey during the 2020-2021 production season. This study includes calculations of energy input, energy output, energy use efficiency, specific energy, energy productivity, net energy, energy input types, GHG emissions and GHG ratio. Survey, observation and data calculations are related to the 2020-2021 production season. The data obtained from the study were collected from 16 different farms (reachable) through face-to-face surveys with full count method. Energy input and energy output were calculated as 19 570.58 MJ/hm2 and 19 471.94 MJ/hm2, respectively. With regards to production inputs, 55.70% of the energy inputs consisted of chemical fertilizers energy (10 900.03 MJ/hm2), 9.46% consisted of chemicals energy (1852.10 MJ/hm2), 9.32% consisted of human labour energy (1823.13 MJ/hm2), 7.65% consisted of electricity energy (1497.28 MJ/hm2), 6.91% consisted of diesel fuel energy (1351.52 MJ/hm2), 4.73% consisted of irrigation water energy (926.10 MJ/hm2), 3.43% consisted of machinery energy (671.98 MJ/hm2), 1.88% consisted of transportation energy (367.72 MJ/hm2), 0.88% consisted of farmyard manure energy (171.80 MJ/hm2) and 0.05% consisted of lime energy (8.94 MJ/hm2). Energy use efficiency, specific energy, energy productivity and net energy were calculated as 0.99, 1.91 MJ/kg, 0.52 kg/MJ and –98.64 MJ/hm2, respectively. The consumed total energy input in production was classified as 28.60% direct energy, 71.40% indirect energy, 14.93% renewable energy and 85.07% non-renewable. Total GHG emissions and GHG ratio were calculated as 1683.24 kgCO2-eq/hm2 and 0.16 kg CO2-eq/kg, respectively.Keywords: energy use efficiency, greenhouse gas emissions, greenhouse gas ratio, peach, TurkeyDOI: 10.25165/j.ijabe.20231602.7917Citation: Demir C, Gökdoğan O. Determination of energy use efficiency and greenhouse gas emissions in peach production. Int J Agric & Biol Eng, 2023; 16(2): 165-170.